The quality perceived in an Information Safety System - Quintella, Heitor Luiz Murat de Meirelles; Liduino de Mello, Marcio Luiz (Revista Gestão da Produção Operações e Sistemas, 2008)
With the identification of information as an increasingly more important asset, its protection has become strategic for companies. This article studies and measures the users perception of the Quality of an Information Security System. The SERVQUAL scale was used for this, following the orientation of Parasuramasn, Zeithaml e Berry. The deductive hypothetical procedure methodology is used and the hypothesis is tested using t-student for small samples, with a 5% significance level. A significant sample of Inmetro managers verified that the perceptions of information security are below expectations. With the results found in this study, it can be affirmed that there are differences between the perceptions and the expectations that users have of the Quality of an Information Security System. Keywords: Quality; Information Security; Competitive Advantage